Autogenous Aedes togoi sub-colony (Chanthaburi, Thailand strain), an efficient laboratory vector in study of filariasis - Riyong D. (2014)
Comparative filarial susceptibility and biology between stock colony and selectively autogenous Aedes. togoi sub-colony were carried out to determine the laboratorial vector-capacity and viability of autogenous sub-colony. The results of susceptibility revealed that the selectively autogenous Ae. togoi sub-colony yielded higher susceptibility than the stock colony, ie Dirofilaria immitis: susceptibility rates=80.00% [Exp1(F8)] and 76.19% [Exp2(F17)] (autogenous sub-colony), 53.33% (Exp1) and 71.43% (Exp2) (stock colony); Brugia malayi: susceptibility rates=83.33% [Exp1(F17)] and 84.38% [Exp2(F19)] (autogenous sub-colony), 81.25% (Exp1) and 75.00% (Exp2) (stock colony), but not at the level of statistically significant differences except the Exp1 of D. immitis, which was significant difference. In addition, the average No. L3 per infected mosquito in the selective autogenous sub-colony (D. immitis: Exp1=3.37, Exp2=3.19; B. mallayi: Exp1=8.80, Exp2=3.37) was also higher than in stock colony (D. immitis: Exp1=2.44, Exp2=2.73; B. malayi: Exp1=7.85, Exp2=3.02), but not at the level of statistically significant difference. The results of comparisons on some biological aspects demonstrated that most of the cases they have similar biology except the average egg deposition per gravid female of stock colony (130.17+/-43.33) was significantly more than selectively autogenous sub-colony(F9) (94.33+/-13.69), egg length x width 575.62+/-18.06 microm x 186.15+/-9.35 microm of stock colony was significantly larger than selectively autogenous sub-colony(F9) 560.49+/-18.96 microm x 177.99+/-8.40 microm, and mean longevity of adult female of stock colony [41.60(6-61)] was significantly longer than selectively autogenous sub-colony(F9) [35.00(5-39)]. The selectively autogenous sub-colony was established and twenty-two successive generations have been colonized.